Analysis of Credit Sales Policy to Minimize Uncollectible Receivable Risk at Bali Niksoma Boutique Beach Resort in Legian - Ni Putu Rina Krisnawati; I K Sudiartha; I M S A Jaya (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
The purpose of this study is to find out and analyze credit sales policies and to find out how much the allowance for receivable losses should be established at Bali Niksoma Boutique Beach Resort. This research uses qualitative data in the form of Standard Operating Procedures (SOP) and quantitative data in the form of aging schedules and sales data. The analytical tool used in the research is 5C analysis to analyze the crediting standards, credit sales policies using the checklist analysis method to analyze compliance with the credit sales policies, and the reserve method for calculating receivable losses. The results showed that the implementation of credit sales policies had not been carried out optimally, management of Bali Niksoma Boutique Beach Resort has implemented its credit policy, but there are still several policies that have not been implemented properly according to set standards. This can be seen throught the result of the checklist analysis that have been carried out. Meanwhile, for the credit standard, the management has not implemented the 5C principle maximally. The amount of bad debts is classified as high, so it is necessary to establish a reserve allowance for bad debts to minimize the risk of uncollectible accounts.